Waterbirth : - Garland, Dianne (Books for Midwives, 2000)
The book has proven to be an excellent guide to using water in midwifery practice. This second edition has been completely updated and now includes a new chapter on midwifery education, reflecting the learning needs of midwives taking PREP. Other topics covered include midwives' accountability and responsibility, positive health aspects of using hydrotherapy, and fetal and newborn perspectives. Useful appendices provide additional information on hyperthermia, offer guidelines for protecting the mother's back, perspectives on waterbirths worldwide and more